Interphase-specific Phosphorylation-mediated Regulation of Tubulin Dimer Partitioning in Human Cells - Holmfeldt, Per (The American Society for Cell Biology, 2007)
The microtubule cytoskeleton is differentially regulated by a diverse array of proteins during interphase and mitosis. Op18/stathmin (Op18) and microtubule-associated protein (MAP)4 have been ascribed opposite general microtubule-directed activities, namely, microtubule destabilization and stabilization, respectively, both of which can be inhibited by phosphorylation. Here, using three human cell models, we depleted cells of Op18 and/or MAP4 by expression of interfering hairpin RNAs and we analyzed the resulting phenotypes. We found that the endogenous levels of Op18 and MAP4 have opposite and counteractive activities that largely govern the partitioning of tubulin dimers in the microtubule array at interphase. Op18 and MAP4 were also found to be the downstream targets of Ca(2+)- and calmodulin-dependent protein kinase IV and PAR-1/MARK2 kinase, respectively, that control the demonstrated counteractive phosphorylation-mediated regulation of tubulin dimer partitioning. Furthermore, to address mechanisms regulating microtubule polymerization in response to cell signals, we developed a system for inducible gene product replacement. This approach revealed that site-specific phosphorylation of Op18 is both necessary and sufficient for polymerization of microtubules in response to the multifaceted signaling event of stimulation of the T cell antigen receptor complex, which activates several signal transduction pathways.